Proceedings of Middle East Oil Technical Conference and Exhibition 1983
DOI: 10.2523/11480-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Multicomponent Isothermal System for Efficient Reservoir Simulation

Abstract: A new model has been developed specifically to study very large, heterogeneous oil and gas reservoirs. By using unique approaches to the simulation of fluid properties and dual porosity/permeability systems, the model is able to accurately simUlate complex reservoir flow performance that was previously difficult or not feasible to model. Descriptions of the fluid flow characteristics of the model are included in the Appendix. Potential applications to several real field simulation problems are discussed to sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 1 publication
0
19
0
1
Order By: Relevance
“…When matrix-matrix interblock flow is significant (Type-III fractured reservoirs as classified by Nelson, 2001), and must therefore be included in the model, we require a dual-porosity/dual-permeability representation. Models of this type were first introduced by Blaskovich et al (1983) and Hill and Thomas (1985). By adding the matrix to matrix connections, the matrix blocks are no longer isolated, and contribute to the overall fluid flow.…”
Section: Impact On the Reservoir Dynamicmentioning
confidence: 99%
“…When matrix-matrix interblock flow is significant (Type-III fractured reservoirs as classified by Nelson, 2001), and must therefore be included in the model, we require a dual-porosity/dual-permeability representation. Models of this type were first introduced by Blaskovich et al (1983) and Hill and Thomas (1985). By adding the matrix to matrix connections, the matrix blocks are no longer isolated, and contribute to the overall fluid flow.…”
Section: Impact On the Reservoir Dynamicmentioning
confidence: 99%
“…, 17 Gilman and Kazemi,18 and Blaskovich et ai. 19 Pseudocapillary pressures are generated to account for nonuniform properties.…”
Section: Et Ai4 Andmentioning
confidence: 99%
“…Kazemi et al (1976) and Saidi (1983) extended to multiphase flow and developed dual porosity simulators. Later, Blaskovich et al (1983) and Hill (1985) developed dual permeability models which also allow for simulating matrix-to-matrix flow. However, fracture uniformity presumed in these models does not conform to outcrop observations, which indicated that height, length, aperture, spacing, and network connectivity of natural fractures vary substantially in the subsurface.…”
Section: Introductionmentioning
confidence: 99%